2019
DOI: 10.1016/j.omto.2019.07.005
|View full text |Cite
|
Sign up to set email alerts
|

ROS/KRAS/AMPK Signaling Contributes to Gemcitabine-Induced Stem-like Cell Properties in Pancreatic Cancer

Abstract: Poor prognosis in pancreatic cancer (PanCa) is partially due to chemoresistance to gemcitabine (GEM). Glucose metabolism has been revealed to contribute to the therapeutic resistance and pluripotent state of PanCa cells. However, few studies have focused on the effects of GEM on cancer cell metabolism, stemness of tumor cells, and molecular mechanisms that critically influence PanCa treatment. We demonstrate that GEM treatment induces metabolic reprogramming, reducing mitochondrial oxidation and upregulating a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 53 publications
2
39
1
Order By: Relevance
“…AMP-activated protein kinase (AMPK) can regulate cellular energy metabolism, and stimulate ATP generation [36]. Activated AMPK promotes glycolysis and enhances cellular differentiation of tumors [37]. These analysis results provide a basis for HP − GC's molecular mechanisms of AS events and provide a basic theory for subsequent experimental verification.…”
Section: Discussionmentioning
confidence: 95%
“…AMP-activated protein kinase (AMPK) can regulate cellular energy metabolism, and stimulate ATP generation [36]. Activated AMPK promotes glycolysis and enhances cellular differentiation of tumors [37]. These analysis results provide a basis for HP − GC's molecular mechanisms of AS events and provide a basic theory for subsequent experimental verification.…”
Section: Discussionmentioning
confidence: 95%
“… 56 It has been shown that Gemcitabine may induce the stem-like cell properties in pancreatic cancer via the involvement of ROS/KRAS/AMPK signaling pathway. 57 These findings suggest that chemoradiotherapy enhances the stem-like properties of CSCs and the resultant active metastatic colonization.…”
Section: Mechanisms Of Chemoradiotherapy Affecting Tumor Cell Invasiomentioning
confidence: 96%
“…Zhao et al demonstrated that the mechanism behind GEM's ineffectiveness was that after GEM induces NADPH oxidase activation via nuclear factor κB (NFκB), activated NADPH oxidase upregulates ROS production, which targets the K-Ras/MAPK pathway. In KRAS knockdown experiments, K-Ras was shown to be responsible for the GEM-mediated metabolic reprogramming and stemness of CSCs [123]. The K-Ras/JNK axis was shown to play a central role in maintaining CSCs or cancer stem-like cells (CSLCs) in pancreatic cancer [124].…”
Section: Altered Ras Signaling By Mutant Ras Forms In Cancer Stem Cellsmentioning
confidence: 99%